Sediment layer formation and its impact on reducing the ultrafiltration module productivity - Тумин, Александр Николаевич (Technology audit and production reserves, 2014)
The theoretical studies of reducing the productivity of ultrafiltration (UF) modules, due to the formation of a highly concentrated sediment layer on the membrane surface, are given in the paper. The main purpose of the research is to justify the advantage of the tangential filtration over a dead-end when operating the UF module on an industrial scale. The UF module modes are considered and their comparison is given in the paper. An algorithm that allows demonstrating the magnitude of the possible sediment layer formation on the membrane surface in the UF module at the dead-end and tangential module operation, and its impact on reducing the module productivity, is developed and presented. The obtained results can be of practical use to compile operation modes of ultrafiltration systems. This research may be useful for design engineers, as well as for scientists, involved in research in the field of water purification by the UF method.